2007
DOI: 10.1177/097168580701300203
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Work Centrality and Other Life Areas in Israel

Abstract: This unique longitudinal study examines the state of work centrality and other life areas (family, leisure, community and religion) in Israel among the same individuals (n=407) over a 12-year period. A new representative sample (serving as a control group) of the Israeli labour force in 1992-93 (n=942) assists us in exploring whether the changes occurred by cohort, life course or period effect. The restudied sample maturation led to a decrease in the importance of leisure, while the importance of work, famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(97 citation statements)
references
References 20 publications
4
92
0
1
Order By: Relevance
“…This might free-up time and energy resources not spent on work to focus on nonwork roles. Other studies found that work centrality decreases as retirement grows closer (Sharabi & Harpaz, 2007), which speaks for the classic view of career stage theories, in which older workers are assumed to gradually disengage from work (Super, 1990). However, meta-analytic findings showed that older workers usually report higher job involvement (Brown, 1996), higher affective organizational commitment (Meyer et al, 2002) and higher occupational commitment (Lee et al, 2000) compared with younger workers.…”
Section: Exploring Gender and Age Effects In Nwosmentioning
confidence: 96%
“…This might free-up time and energy resources not spent on work to focus on nonwork roles. Other studies found that work centrality decreases as retirement grows closer (Sharabi & Harpaz, 2007), which speaks for the classic view of career stage theories, in which older workers are assumed to gradually disengage from work (Super, 1990). However, meta-analytic findings showed that older workers usually report higher job involvement (Brown, 1996), higher affective organizational commitment (Meyer et al, 2002) and higher occupational commitment (Lee et al, 2000) compared with younger workers.…”
Section: Exploring Gender and Age Effects In Nwosmentioning
confidence: 96%
“…Abramson & Inglehart, 1995;Sharabi & Harpaz, 2007;Smola & Sutton, 2002), we controlled for these variables. Gender (0 = male, 1 = female) and type of organization (1 = private, 2 = public) were measured with dichotomous variables; age, education and seniority were reported in years.…”
Section: Control Variablesmentioning
confidence: 99%
“…To sum up, work centrality in Israel remained stable throughout the research period and it is high compared to other developed countries (see Sharabi and Harpaz 2007b). Work values, as Weber (1958), Veblen (1953) and Child (1981) found, can lead to the decline or success of societies.…”
Section: Discussionmentioning
confidence: 92%
“…In the long run, as we have indicated, the increase in peripheral instrumental values can infl uence core values and lead to a decrease in work centrality. It is probable that the increase in the importance of leisure, as has already happened in the US, Germany, and Japan (Sharabi and Harpaz 2007b), will eventually occur in Israeli society, too, at the expense of the importance of work. Future longitudinal research on work centrality, job satisfaction, and work goals can follow the changes of core and peripheral work values in a changing Israeli society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation